PERSISTENT TRIGEMINAL ARTERY - ANATOMICAL FEATURES AND CLINICAL SIGNIFICANCE - Dodevski, Ace; Zhivadinovik, Julija; Matveeva, Niki; Zafirova, Biljana; Chadikovska, Elizabeta; Trpkovska, Biljana; Paunkoska, Anamarija; Aliji, Vjolca; Dimitrovska, Maja Jakimovska; Jovanovska, Elizabeta Stojovska; Cangovska, Tatjana Cepreganova (Journal of Morphological Sciences; Vol 6 No 2 (2023): JMS, 2023)
Persistent trigeminal artery is the most common primitive carotid basilar anastomosis that persists in adulthood. The overall incidence of persistent trigeminal artery is between 0.2 to 0.76%. PTA are known to be associated with a wide range of pathology. The aim of this study was to describe the morphological characteristics of the PTA and to emphasize its clinical significance. We examined radiographs from patients who had CT angiography undertaken for a variety of clinical reasons, performed as a part of their medical treatment at the University Institute for Radiology in Skopje, RN Macedonia. The study population included 234 patients, 130 male and 104 females, mean age 57.8 years. In one patient we found PTA with overall incidence of 0.42%. CTA revealed a left PTA that arise from the internal carotid artery and communicate with the basilar artery between the origin of the anterior inferior cerebellar artery and the superior cerebellar artery. Although anatomically interesting, an awareness of the anatomy and variations of the brain arteries is clinically important for radiologists and surgeons for save performance of procedures, and forensic pathologists since variants may have forensic consequences.  Key words : anatomy, persistent trigeminal artery, computed tomography.